INTENSIVE ENGLISH PROGRAM AT CAMBRIDGE ENGLISH COURSE PARE KEDIRI - Qodariah, Siti Nurlailatul (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
The aims of this research is to describe the intensive English program at CEC pare kediri, it includes the background of intensive English program, the teachers’ background of intensive English program, the implementation of intensive English program, the students’ responds on intensive Enlish program, and the Problem and solution of intenisve English program. This research used qualitative descriptive design. This research used some data collections those are interview, observation and documentation. From the result, it can be concluded that the background of intensive English program is to meet the needs of students who want a short English courses. Teachers’ background of intensive English program is graduate students’ of Mastering System BEC. The implementation of teaching intensive English program must first be prepared is the syllabus and schedule, every morning the students have English morning and the students have four classes each day. Intensive English program using contextual teaching learning methods and drilling technique, the media used are audio and audio-visual. The students’ reponds toward intensive English program is very good and satisfying. The problems that arises were the difficulty of disciplining the students to speak English every day and the prohibition to bring the mobile phone but all of these problems could be solved well.